Reviewing the landscape of research on influencer-generated content - Chen, Xiaoyu (2020)
The purpose of this paper is to review and synthesize scholarly articles on influencer-generated content. Specifically, it attempts to identify: (1) theoretical foundations that have been used, (2) research methods that have been employed, and (3) research foci and future directions. Based on the in-depth content analysis of 167 related articles, this paper finds that 5 commonly used underpinning theories, namely, selfpresentation theory, online information processing theory, knowledge persuasion theory, signaling theory, and warranting theory. Primary and secondary research data from diverse sources, quantitative and qualitative analysis approaches have been employed by the articles. Current research foci include three clusters-identifying social media influencers, investigating influencers' motivations for creating content and assessing the social and economic impacts of influencer-generated content. Correspondingly, three research perspectives-content creator perspective, content generation perspective, and content impacts perspective are adopted to guide the future directions.